UPAYA PEMENUHAN KEBUTUHAN AIR BERSIH KEPERLUAN RUMAH TANGGA DESA MERAK BATIN - Olivia Avriliani; I Gede Sugiyanta; Irma Lusi Nugraheni (JPG (Jurnal Penelitian Geografi), 2013)
This study aimed to describe the efforts of residents in the Merak Batin Village Natar South Lampung District in meeting the water needs of domestic use, the study points to the source tap water, the amount of water needs, and residents get clean water efforts. The research object is the head of the family in the village of Merak Batin South Lampung District of Natarian. Collecting data using observation, unstructured interviews, questionnaires and documentation. Results of this study indicate that: (1) there are 4 source of clean water in the Merak Batin village, namely dug wells, boreholes, rainwater harvesting, and public wells. (2) The average number of needs of water/capita/day (liters) in the village of Inner Peacock is 56 liters, which is not in accordance with WHO standards (60 liters). (3) Efforts to clean water by way of purchase is divided into two ways: delivered by the seller (55.67 %) and take themselves (44.33%).Penelitian ini bertujuan untuk untuk mendeskripsikan upaya-upaya penduduk di Desa Merak Batin Kecamatan Natar Kabupaten Lampung Selatan dalam memenuhi kebutuhan air bersih keperluan rumah tangga, dengan titik tekan kajian pada sumber air bersih, jumlah kebutuhan air bersih, dan upaya penduduk mendapatkan air bersih. Objek penelitian adalah kepala keluarga di Desa Merak Batin Kecamatan Natar Kabupaten Lampung Selatan. Hasil penelitian menunjukkan bahwa: (1) Sumber air bersih di Desa Merak Batin terdapat 4, yaitu: sumur gali, sumur bor, penampungan air hujan, dan sumur umum. (2) Rata-rata jumlah kebutuhan air bersih/kapita/hari (liter) di Desa Merak Batin adalah 56 liter, yang mana tidak sesuai ketentuan standar WHO (60 liter). (3) Upaya mendapatkan air bersih dengan cara membeli dibagi menjadi dua cara yaitu diantar oleh penjual (55,67%) dan mengambil sendiri (44,33%).Kata kunci: kebutuhan air bersih, rumah tangga, upaya pemenuhan